(untitled) (Nepal Journal of Neuroscience, 2023)
Introduction: Stiff Person Syndrome is a rare autoimmune neurological disorder with chronic muscle spasms leading to chronic pain and debilitation. Case Report: We describe a case of a 57-year-old man with the history of Diabetes mellitus type 1 diagnosed 15 years back with high-titer positive anti-GAD antibodies and poorly controlled blood sugar levels under highly dosed insulin treatment. Discussion: Intrathecal baclofen showed a marked improvement for the relief of spasticity with the choice of a baclofen pump for similar patients.